Incorporation of water-soluble and water-insoluble ruthenium complexes into zirconium phosphate films fabricated by the layer-by-layer adsorption and reaction method - Wang, Qifeng (Langmuir : the ACS journal of surfaces and colloids, 2008)
Water-soluble tris(2,2'-bipyridine)ruthenium(II) complex (Rubpy) and water-insoluble tris(4,7-diphenyl-1,10-phenanthroline)ruthenium(II) complex (Rudpp) were successfully incorporated into zirconium phosphate (ZrPS) films fabricated by a facile layer-by-layer (LbL) adsorption and reaction method. Rubpy-incorporated ZrPS films were fabricated by the LbL adsorption and reaction method employing a mixture solution of Rubpy and phosphate salt. Rubpy was incorporated into ZrPS films during the formation of ZrPS layers because of the electrostatic interaction between them. Rudpp was dissolved in the mixture solution of aqueous phosphate salt and ethanol and was incorporated into ZrPS films through the formation of ethanol preintercalated ZrPS layers. The successful incorporation of Rubpy and Rudpp into ZrPS films was confirmed by UV-vis absorption spectroscopy. Rubpy and Rudpp have concentrations of 0.915 x 10 (14) and 3.23 x 10 (14) molecules/cm (2) in each ZrPS layer, respectively. Scanning electron microscopy measurements indicate that the as-prepared Rubpy-incorporated ZrPS films are smooth while the as-prepared Rudpp-incorporated ZrPS films are porous. The porous Rudpp-incorporated ZrPS films are suitable to use as oxygen sensors because the luminescence of Rudpp incorporated into the ZrPS films can be quenched by oxygen and the porous film structure facilitates the permeation of oxygen into and out of the film